(3TQM GddeYIs - (3GdHjGJj, GdfLaj, GdCMeOj, edG cJGH, eMeO LhGO Hf eMeO Jbj Hf eMeO, (B( (3cGf MjG (B1267 (3g` (B)s
(3ChdgG (B:s
.. (3hCeG GdQhGjI aEfeG Jchf OdjdG Ydi Cfg NdGa ddCaVd HYOe aQV GdZOjQ GdeSFhd Yfg djS ef Gdbdjd aEf bhd GdSGFd ajSJMe efg Ch jZJSd Shi Yf LhGR GdGSJfLGA hGdZSd (B....s
(3BNQgG (B:s
.. (3aEf GdeOGQ aj GdJecf Ydi GQJaGY GdefY GdMSj hGdTQYj hdPG CHjM GdJjee eY Nha GdVQQ hEf bOQ Ydi GdGSJYeGd GdKGfj jLhR GdYOhd Edi (B...s
(3JHUQI GdYfhGf (B:s
(3PcQ Bb HQRc WgQGfj GNJdGa YfhGf GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\201s
(3GdPQjYI (B2 - 243 ( 1700)s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis